1987
DOI: 10.1002/1097-0142(19870301)59:5<952::aid-cncr2820590517>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of pepsinogen a isozymogens, serum pepsinogen A and C levels, and serum gastrin levels

Abstract: Gastric mucosal pepsinogen A phenotype, serum pepsinogen A level, serum pepsinogen C level, serum pepsinogen A/pepsinogen C ratio, and serum gastrin level were evaluated as potential markers for gastric cancer or its precursors in 19 healthy volunteers and 341 patients from the gastroscopy program. Gastric cancer, atrophic gastritis, and intestinal metaplasia of the stomach were associated with pepsinogen A phenotypes, characterized by an intense fraction 5, and with a low serum pepsinogen A level (less than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…In the previous studies, no cut-off values were demonstrated to be related to serum PG I level and PG I / PG II ratios. In similar studies on this subject, different cut-off values were used, and the sensitivity and specificity were reported to range from 74.3-93% and 68.4-100%, respectively [8,[19][20][21][22]. The current study shows that cut-off values for the serum PG I level <25 ng/ml and the serum PG I / PG II ratio <3.0 would be convenient and meaningful for stomach cancer and atrophic gastritis screening.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the previous studies, no cut-off values were demonstrated to be related to serum PG I level and PG I / PG II ratios. In similar studies on this subject, different cut-off values were used, and the sensitivity and specificity were reported to range from 74.3-93% and 68.4-100%, respectively [8,[19][20][21][22]. The current study shows that cut-off values for the serum PG I level <25 ng/ml and the serum PG I / PG II ratio <3.0 would be convenient and meaningful for stomach cancer and atrophic gastritis screening.…”
Section: Discussionmentioning
confidence: 79%
“…Both of these types are produced in the essential cells in the stomach corpus and fundus and in mucous cervical cells. Unlike PG A, PG C is also produced in the Brunner glands in the proximal duodenum and in the pyloric glands in the antrum [8]. Serum pepsinogen levels reflect the morphological and functional status of the stomach mucosa, so they serve as markers of chronic atrophic gastritis [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of serum pepsinogen I levels as an assessment of gastric acid secretion was adopted as early as in 1985 [13,14]. The clinical significance of pepsinogen A and pepsinogen C and serum gastrin levels [15] and the role of serum pepsinogen I and serum gastrin in the screening of severe atrophic corpus gastritis had been studied [16] and in screening of atrophic pan gastritis with high risk of cancer [17]. PGI reflects the status of the mucosa of the corpus and fundus of the stomach and is a wellknown indicator of the corpus mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The serum PG I/II ratio is also reduced in gastric carcinoma, as pepsinogen I decreases proportionally more than pepsinogen II. In contrast, the serum level of gastrin is increased in atrophic corpus gastritis [15]. In Japan, where studies have shown a high prevalence of chronic gastritis, serum pepsinogen has been studied as a mass screening tool for the detection of gastric cancer [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%